Developmental tendencies of the European Union’s antitrust law enforcement policy on digital markets – from the European Commission’s decision in the Google cases to the sectoral regulation - Kolasiński, Marek (Studia Iuridica Toruniensia, 2023)
The article identifies developmental tendencies in the European Union’s antitrust law enforcement policy on digital markets. The author begins his argument by outlining a series of the European Commission’s decisions regarding Google’s market practices and by analysing the theoretical and legal assumptions on which the judgment of the General Court of the European Union in the Google Shopping case is based, and subsequently attempts to present the market effects of the actions in question undertaken by the EU’s competition authorities. The author is sceptical about the economic effectiveness of the European Commission’s decisions and draws attention to the risks associated with increasing antitrust interventionism. In particular, the publication indicates the risk of excessive relaxation of the analytical discipline in antitrust cases. However, the article expresses the approval for legislative actions aimed at including digital markets in sectoral regulation. The author believes that such a solution will make it possible to achieve generally accepted public goals, and does not pose threats related to further tightening of the antitrust law enforcement policy.